Efektifitas Penggunaan Gerobak Sorong Bermesin Model Track untuk Mengangkut Buah Sawit di Kabupaten Musi Banyuasin - Stenia Ruski Yusticia (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
Transportation of oil palm Fresh Fruit Bunches (FFB) from the plantation to the harvest collection point (HCP) must be done as quickly as possible. This is due to an increase in free fatty acids after the FFB is harvested. Some of the obstacles found were the FFB transportation equipment which was not yet capable of reaching the fruit in the garden easily and the transportation time which was quite long due to the uneven road conditions. With technological advances and the rapid development of innovation, the discovery of track model wheelbarrows that use a driving engine means that further studies are needed to determine the effectiveness of these transport machines. In this research, we will compare wheelbarrows without engines and wheelbarrows with track models, there are 3 (three) treatments given, namely on flat roads, bumpy roads and damaged roads. Researchers search for and collect data on transport capacity, transport load, transport speed and transport costs. The results of this research show that carrying capacity and road conditions have a effect on travel time and speed. This is due to the ability/power of the machine which is quite large and stable in transporting fruit. and, other results from this research show that the use of motorized wheelbarrows can reduce transportation costs because the transportation speed increases so that the travel time is shorter.